The mathematics behind a continuous time : principal - agent model (2017)
The theory of incentives has been one of the major developments in the economic literature in the last forty years. This branch of economics analyzes agency problems that arises when two individuals engage in a risk sharing situation under conditions in which their private knowledge affect the outcome. This paper studies the recent development of new methods for analyzing continuous time dynamic models using stochastic calculus. In particular, I analyze the Sannikov (2008) continuous time principal-agent model, in which the output is a diffusion process with drift determined by the agent's unobserved effort. I describe the mathematical framework behind the model, I characterize the optimal contract and provide new insights that the discrete version of the model could not.--Tomado del Formato de Documento de Grado.